Industrial Nostalgia: The Case of Poldi Kladno - Gibas, Petr (Lidé města, 2008)
In the last few years, industrial architecture has started to attract more attention than probably ever before. In order to pursue the issue of growing aesthetic interest in the industrial landscape I analyze contemporary visual and related discoursive representations of industrial architecture and industrial landscape in the Czech Republic. Discussing the case of a vast industrial brownfield adjacent to the town center of Kladno, a former industrial city in Central Bohemia, I try to show how the industrial architecture is in fact aestheticized. By questioning what lies behind such aestheticization I want to show how industrial landscape and the past it embodies have been negotiated within the urban space. I perceive the visual as well as discoursive representations of industrial architecture as predominantly melancholic and nostalgic. My argument is, however, that nostalgia does not have to present a weakness since it originates in the image we hold of our past and it embodies our fears about our future. It can thus serve as a position from which we could critically question our present-day existence and our potential futures. Our aesthetic perception has been changing. The discussion of the reasons why it has been happening and what lies behind such changes is needed since it relates to the wider discussion about our relationship with the past and thus also about the image we have of ourselves.